Pelaksanaan Administrasi Sarana Prasarana Dalam Meningkatkan Hasil Belajar Peserta Didik Madrasah Al – Islah Karawang - Putri, Siti Alaidah; Abdurrohim, Abdurrohim; Mustofa, Taufik (Jurnal Ilmiah Wahana Pendidikan, 2024)
At Madrasah Al-Islah Karawang, the implementation of Facilities and Infrastructure Administration is crucial. Well-maintained and clearly utilized facilities are especially important during learning activities when school facilities and infrastructure are in use. While delivering the framework, the school is responsible for involving the Head and Leaders of the Madrasah who directly manage and handle the services and foundation. A qualitative research method is used in this approach. Interviews, observations, and documentation are all components of data collection. Comparative data analysis is used in this study. When the school aims to maximize student goals and learning outcomes of Madrasah Al-Islah Karawang students, it is essential to utilize and maintain school facilities and infrastructure administration as it is the main core that can support and streamline the education process or the teaching and learning process. One of the key factors determining the success and quality of education is the quality of the educational institution. The facilities and infrastructure managed by teachers and staff have been implemented at Madrasah Al-Islah Karawang. Madrasah Al-Islah Karawang frequently updates various areas, including facilities and infrastructure, along with the progress in education.